2014
DOI: 10.1002/mar.20721
|View full text |Cite
|
Sign up to set email alerts
|

Pièces de Résistance? Core and Casual Consumers’ Valuations of Aesthetically Incongruent Artworks

Abstract: Research in consumer psychology suggests that there is limited room for acclaimed producers or brands to experiment with the aesthetic appearance and design of their products. This premise is rooted in consumers’ preference for aesthetic congruity and the cognitive difficulty associated with evaluating incongruent offerings. Yet examples of successful artists whose work clearly defies the imperative of congruity do exist. Although these artists are the exception rather than the rule, their success suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Since the identification of the intrinsic qualities of products and producers in the creative industries is complicated by widespread uncertainty on both the demand and supply sides (Caves, 2000;Hirsch, 1972), the combinatorial and aesthetic nature of style can firmly guide people's understanding and evaluation. Althuizen and Sgourev (2014) are clear on this point. Creative industries are contexts "where innovation and the forging of a distinct style are necessary to attract attention and establish a reputation" (2014, p. 605).…”
Section: Empirical Setting and Hypothesesmentioning
confidence: 96%
“…Since the identification of the intrinsic qualities of products and producers in the creative industries is complicated by widespread uncertainty on both the demand and supply sides (Caves, 2000;Hirsch, 1972), the combinatorial and aesthetic nature of style can firmly guide people's understanding and evaluation. Althuizen and Sgourev (2014) are clear on this point. Creative industries are contexts "where innovation and the forging of a distinct style are necessary to attract attention and establish a reputation" (2014, p. 605).…”
Section: Empirical Setting and Hypothesesmentioning
confidence: 96%
“…And a study by Pocheptsova et al (2010) found a positive association between increased cognitive effort (or disfluency) and perceived originality, but only for exclusive products. Status cues may interfere in evaluative processes by generating arousal or interest and/or evoking associations with producer effort or skill (Althuizen & Sgourev, 2014). For example, a Louis Vuitton bag with a simple aesthetic design may still produce sufficient arousal and evoke positive associations with the amount of effort or skill that went into its design.…”
Section: Studymentioning
confidence: 99%
“…This is a particularly important finding as the human brand can control his/her extension strategy. It is also important in view of existing results in the product brand literature, which conclude on the negative role played by moderate levels of incongruence when the performance is poor (Roedder John et al, 1998) or by stronger levels of incongruence for core customers (Althuizen and Sgourev, 2014) on brand identity dilution. We also build on past research stating the difficulty of convincing internal stakeholders to accept incongruent extension projects (Phillips and Zuckerman, 2001) and we conclude that once these are achieved, the social rewards generated can be higher than for congruent extension projects, at least for the expectancy dimension of congruence, i.e.…”
Section: Conceptual Contributionsmentioning
confidence: 99%